Analyzing the production activity of banking institutions in Libya : Productivity and efficiency determinants / Khalad M. S Alrafadi - Alrafadi, Khalad M. S (Institute of Graduate Studies, UiTM, 2016)
Measurements of banking efficiency and productivity have received increasing efforts in applied economics in recent years due to the rapid acceleration of changing nature of financial industry. The financial sector, especially the banking system, plays a central role in the process of economic development and growth in a specific country. The efficiency of the banking system is one of the most important issues in the financial market because the efficiency of banks could affect the stability of the banking industry and thus the effectiveness of the whole monetary system in a country. Bank’s efficiency is measured as the difference between the bank’s position and its best production frontier. Generally, there are two main techniques that would be used to evaluate banking efficiency: parametric and non-parametric techniques. This study analyzed the technical efficiency and productivity of the banking sector in Libya during the period from 2004 until 2010. A nonparametric data envelopment analysis (DEA) method is employed to estimate the mutually exhaustive components namely pure technical efficiency (PTE) and scale efficiency (SE) of the 17 banks in Libya. Also, the Total Factor Productivity (TFP) of the Libyan banks is calculated using the Malmquist Productivity Index (MPI)…